Esophagitis Dissecans Superficialis in Children. Issue 2 (August 2021) - Ebigbo, Nonyelum; Park, Jason Y.; Cheng, Edaire; Gurram, Bhaskar
ABSTRACT: Objectives: Esophagitis dissecans superficialis (EDS) is a desquamative disorder of the superficial esophageal epithelium with variable clinical characteristics. Endoscopically, there is an appearance of superficial peeling of sheets of epithelium. Histologically there is 2-toned epithelium with coagulative necrosis of the superficial epithelium. Currently, there is paucity of data regarding this condition in children. Methods: A 10-year retrospective search of the pathology information system was performed for cases with a pathologic diagnosis of EDS in a tertiary care pediatric center. Demographic data, clinical history, endoscopic findings, and histopathologic reports were reviewed. Results: Thirteen patients (9 girls; ages 3–18 years), were identified with histologic findings of EDS. Esophageal food impaction, dysphagia, vomiting, and abdominal pain were the most common presenting symptoms. Sixty-nine percentage of the patients had underlying comorbidities and 76% were on at least 1 medication chronically. Eosinophilic esophagitis (23%), inflammatory bowel disease (23%), and gastroesophageal reflux disease (GERD) (15%) were the most common associated diagnoses. Of the 13 patients, 5 had repeat endoscopies showing complete resolution of EDS with no complications. Conclusions: EDS is an under-recognized entity that endoscopists should be familiar with. In our series, the most prevalent associations were with food impaction and eosinophilic esophagitis (EoE). Contact injury and/or inflammation may precede the development of EDS. Pediatric EDS appears to be an incidental finding without significant morbidity or mortality.